PENERAPAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA DALAM MATA KULIAH PRAKTIK MEKANIKA TANAH - Hanifa Khairunnisa (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This article discusses the implementation of Problem Based Learning (PBL) in the Soil Mechanics practical course for students of the Building Engineering Education Program (PTB) at Universitas Negeri Jakarta. PBL is considered an effective learning model in developing critical thinking skills, problem-solving abilities, and the application of knowledge in real-world contexts. A quantitative descriptive research method was employed using a questionnaire to evaluate students' understanding of soil mechanics material. The analysis results indicate that the majority of students rated their understanding as lacking or very lacking. Therefore, PBL is proposed as a solution to enhance learning effectiveness. The concrete steps of PBL in soil mechanics practice are also outlined in this article, along with its potential implications for student learning experiences.